Pengaruh Financial Knowledge, Financial Risk Tolerance, dan Digital Financial Literacy Terhadap Investment Behavior Generasi Z - Fenny Fenny; Montigor Afrizal Purba (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rapid expansion of digital financial platforms has altered the way young individuals engage in investment activities, particularly among Generation Z. This study examines how financial knowledge, financial risk tolerance, and digital financial literacy shape investment behavior among Generation Z in Batam City. A quantitative approach was applied through a survey method, using primary data collected from 100 respondents selected via purposive sampling. The respondents consisted of individuals aged 14–28 years who demonstrated interest in or prior involvement with digital investment instruments. The collected data were processed using multiple linear regression analysis with SPSS to evaluate both individual and joint effects of the independent variables on investment behavior. By focusing on Generation Z in a rapidly developing urban area, this study provides contextual empirical evidence on investment decision-making in the digital finance environment. The findings are expected to offer academic insights while also serving as a practical reference for educational institutions, financial regulators, and financial service providers in designing initiatives aimed at strengthening financial and digital financial literacy to support more rational and sustainable investment practices.